2013
DOI: 10.1007/s10964-013-9909-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Collective Efficacy on Risks for Adolescents’ Perpetration of Dating Violence

Abstract: Given prevalence rates and negative consequences that adolescents' perpetration of dating violence may have on an individual's well-being and future relationships, it is imperative to explore factors that may increase or reduce its occurrence. Thus, we aimed to identify how multiple contextual risk factors (individual, family, schools, and neighborhoods) were related to adolescents' perpetration of dating violence over a 6 year period. Then, we assessed how neighborhood collective efficacy, an important predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 67 publications
1
43
0
1
Order By: Relevance
“…Fifteen of the 20 studies recruited participants from school settings, although some of those also recruited from non–school based settings. To assess DV, five studies used modified versions of the Conflict Tactics Scales, 8,38,40,43,48 four used the Safe Dates Scale, 6,37,39,49 and nine used one- or two-item queries about aggressive acts. 9,3436,42,4447 The remaining two studies used the Abusive Behavior Inventory 41 and the Abuse Assessment Screening Tool.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen of the 20 studies recruited participants from school settings, although some of those also recruited from non–school based settings. To assess DV, five studies used modified versions of the Conflict Tactics Scales, 8,38,40,43,48 four used the Safe Dates Scale, 6,37,39,49 and nine used one- or two-item queries about aggressive acts. 9,3436,42,4447 The remaining two studies used the Abusive Behavior Inventory 41 and the Abuse Assessment Screening Tool.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…9,3436,42,4447 The remaining two studies used the Abusive Behavior Inventory 41 and the Abuse Assessment Screening Tool. 20 Eleven studies examined demographic and structural characteristics, 8,20,37,38,4349 12 examined neighborhood disorder, 6,8,9,20,35,36,3943,49 and eight examined social disorganization. 6,8,9,34,35,43,48,49 …”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Manning, Davies, and Cicchetti (2014) studied a sample of very young children across the transition from toddlerhood (2 years of age) to early childhood (4 years of age), noting that IPV increased externalizing behavior problems, particularly in the absence of sensitive maternal behavior. Other research, however (Schnurr & Lohman, 2013), argued against longterm effects of early childhood exposure to IPV. These inconsistent results highlight the need for additional research examining the mechanisms and potential moderators of very young children's responses to IPV.…”
Section: Ipv Effects On Children's Behavior Regulationmentioning
confidence: 99%
“…The only study to examine social control as a contextual moderator found that neighborhood collective efficacy, defined as community social cohesion and willingness to intervene for the common good, did not moderate the association between a composite measure of substance use and PDVP assessed 6 years later 42 ; however, that study did not distinguish among specific substances, and focused on the distal effects of early substance use on later PDVP. Previous research using the same data source as the current study found that the association between HALC and PDVP was moderated by family and peer violence, but not neighborhood violence.…”
Section: Introductionmentioning
confidence: 99%